Estimation of grain resistance of various wheat types to corn bug Eurygaster L. (Hemiptera, Scutelleridae) - A. V. Kapustkina (Зерновое хозяйство России)
In Russia wheat is a strategically important food and export grain crop, but despite the expansion of sown areas and the growth of gross yields, yield quality remains low. A significant decrease in the quantitative and qualitative characteristics of the wheat grain productivity is caused by corn bug Eurygaster L. Planting resistant varieties is one of the most environmentally friendly and effective ways to reduce the number and harmfulness of corn bug. Unfortunately, modern wheat varieties are often not characterized by corn bug resistance, although this is of paramount importance for grain production and breeding programs. The purpose of the current study was to compare the damage caused by corn bugs to grain of different wheat types and varieties. In accordance with GOST 33538-2015 “Plant protection. Methods for identifying and accounting for damaged grains by corn bug”, there has been conducted an estimation of wheat samples for their damage by corn bug. There has been shown that corn bug Eurygaster L. equally damages grain of different wheat types, varieties, and forms. Among the 108 studied wheat varieties, only 16 varieties were characterized by a low degree of grain damage. Absolutely resistant varieties to damage by corn bug have not been identified. The least mean grain damage by corn bug was found in such varieties (up to 5.0 %) as ‘Utrish’, ‘Yunion’, ‘Altaiskaya zhnitsa’. There has been established that the largest number of grain samples slightly damaged by corn bug was found among spring durum wheat varieties (up to 50.0 %). There has been determined that under different agroclimatic conditions of cultivation, the most studied wheat samples had the same level of grain damage by corn bug.